Analisis Trend Penelitian Penggunaan Algoritma Penjadwalan serta Faktor yang Mempengaruhinya: Analisis Bibliometrik R dan Pemetaan VOSviewer - Dwi Novia Al Husaeni; Jajang Kusnendar (Departemen Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2025)
Scheduling is one method used to avoid problems with the operating system. Scheduling has various algorithms including Round Robin, First in First out, and SJF. This research aims to analyze the literature review of scheduling algorithm research trends and the factors that influence them through R bibliometric mapping analysis on research that has been published in Scopus and Google Scholar indexed journals from 2019 to 2023. The method used in this research is R bibliometric analysis . Publish or perish is used as a search application and VOSviewer is used as a data mapping application. The results of the research show that the development of the number of research publications regarding Scheduling Algorithms indexed by Google Scholar from 2019 - 2023 has decreased quite significantly (383 (2019), 314 (2020), 195 (2021), 84 (2022), and 20 (2023). )). Meanwhile, based on the Scopus database, research developments regarding scheduling algorithms experienced fluctuations, namely decreasing in 2021 (200 articles) and increasing in 2022 (830 articles). In 2020 there was a significant decline. Based on the VOSviewer mapping results, it is known that the process scheduling algorithm that is widely used for research is the Round Robin (RR) algorithm which is in cluster 1, cluster 3, and cluster 7. The reason why the RR algorithm is in good condition. This request is because it is able to provide fairness in divides CPU processing time between running processes.